Sorption of Some Heavy Metal Ions by Chitosan and Chemically Modified Chitosan - Jideowno, A.; Okuo, J. M.; Okolo, P. O. (Biological Sciences - PJSIR, 2006)
Chitosan was produced by deacetylation of chitin with sodium hydroxide at a temperature of 117 °C (Randal et al, 1979). In this study, chitosan was prepared from African giant land snail (Archachatina marginata), and acrylamide was grafted onto the chitosan to produce chitosan grafted acrylamide (cga). The two varieties (chitosan and cga) were separately used as adsorbents for the removal of some heavy metal ions (Pb2+, Cd2+, and Ni2+) from aqueous systems. The amount of metal ions (Pb2+, Cd2+, and Ni2+) adsorbed onto chitosan at optimum temperature (45 °C) ranged from 43.88-60.60 %, 27.50-58.60% and 41.30-58.90%, respectively. That adsorbed onto cga ranged from 49.40-65.56%, 56.50-97.90% and 29.60-64.80%, respectively. Results revealed that cga sorption capacity was approximately twice as high as chitosan.